The epifascial cap: A typical imaging sign for subcutaneous granuloma annulare in children - Beqo, Besiana P.; Tschauner, Sebastian; Gasparella, Paolo; Brcic, Iva; Haxhija, Emir Q. (Frontiers in Pediatrics, 2023)
Objectives. Subcutaneous granuloma annulare (SGA) is a rare, self-limiting granulomatous disease in children, commonly diagnosed by histopathology following biopsy or surgical excision. This study aimed to identify imaging clues for SGA that could expedite accurate diagnosis and avoid the need for biopsy in children. Methods. We retrospectively analyzed complete hospital records of all children diagnosed with SGA at our institution from January 2001 to December 2020. Detailed disease history, imaging findings, management, and outcome were evaluated. Results. We identified 28 patients (20 girls) at a median age of 3.75 (range 1–12.5 years). Ten patients presented with multiple lesions. Most lesions were located on the lower extremities (n=26/41). Ultrasound examinations were performed on all patients, and 12 (43%) patients also received an MRI. Surgical intervention was conducted in 18 (64%) patients either by incisional biopsy (n=6) or total excision of the lump (n=12). In all patients who did not undergo surgery, SGA resolved spontaneously. A careful review of the MRIs led to the discovery of a characteristic imaging shape of SGA lesions: the epifascial cap with a typical broad circular base laying on the fascia, extending towards the subdermal/dermal tissue. This distinctive shape was evident in every patient in our cohort. Conclusions. The "Epifascial Cap Sign" is a specific imaging sign for SGA, which to the best of our knowledge, helps distinguish this disease from other subcutaneous lesions. Recognition of this novel diagnostic sign combined with the historical and physical findings should enable clinicians to establish SGA diagnosis easily and diminish the need for further invasive diagnostic procedures.